PEMANFAATAN VIRTUAL REALITY UNTUK PENGEMBANGAN KIOS INFORMASI OBJEK WISATA DI KOTA PEKALONGAN BERBASIS MOBILE - Much. Rifqi Maulana; Christian Yulianto Rusli; Ichwan Kurniawan (JURNAL LITBANG KOTA PEKALONGAN, 2016)
LIMITATIONS OF MEDIA INFORMATION ABOUT TOURISM IN PEKALONGAN CITY CAUSES PROBLEM FOR TOURISTS TO GET INFORMATION THAT IS ACCURATE, TIMELY AND RELEVANT OF ATTRACTIONS TO BE VISITED. BY USING VIRTUAL REALITY IN THE FORM OF VIRTUAL TOUR 360º PANORAMAS AS A MEDIUM OF INFORMATION ABOUT THE CITY'S ATTRACTIONS PEKALONGAN CAN ALLOW TOURISTS CAN SEE THE PICTURE SIGNIFICANTLY ABOUT TOURIST ATTRACTIONS TO BE VISITED AND TOURISTS CAN SEE INFORMATION ABOUT TOURIST ATTRACTIONS IN THE CITY OF PEKALONGAN CLEARLY, WHENEVER AND WHEREVER BECAUSE OF MEDIA INFORMATION ARE DISPLAYED BASED ON MOBILE. INFORMATION KIOSK APPLICATION DEVELOPMENT STAGE USING MULTIMEDIA SYSTEM WITH A FLOATING STAGE, CONCEPT, DESIGN, COLLECTION OF MATERIALS, MANUFACTURE, TESTING AND DISTRIBUTION. BASED ON INTERVIEWS WITH RELATED AGENCIES SUGGEST THAT THE ATTRACTION WILL BE CREATED VIRTUAL TOUT 360º PANORAMAS ARE 6 OBJECTS THEY ARE WISATA BAHARI 5 SPOT, PASIR KENCANA 5 SPOT, PANTAI SARI 2 SPOT, KAMPUNG BATIK KAUMAN 26 SPOT, GROSIR BATIK SETONO 6 SPOT AND MUSEUM BATIK 12 SPOT. AT THE STAGE OF TESTING THE SYSTEM USING A TEST GRAPHICAL USER INTERFACE (GUI) AS THE TESTING SYSTEM OF THE DEVELOPER SIDE, RESULTING THAT THE APPLICATION CAN BE RUN WITH EITHER SUITABILITY BUTTONS AND A DISPLAY ACCORDING TO THE FUNCTIONS. WHEREAS THE CONCLUSION IS SUPERBLY CREATION KIOSK APPLICATION INFORMATION BY USING VIRTUAL REALITY ATTRACTIONS IN THE CITY OF PEKALONGAN BASED MOBILE.